(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The contributions gathered in this volume through the efforts of Ms. Mirela-Luminiţa Murgescu—and, naturally, through the merit of the authors (most of whom are graduates of the advanced studies program in the "history of ideas and mentalities" at the Faculty of History, University of Bucharest)—align with what we may hope is becoming a new course for Romanian historiography. By "new course," I do not mean a well-defined path—and certainly not a mandatory one—but rather a new mindset. I have in mind a historian conscious of the boundless possibilities of their profession, of their freedom and responsibility, and of the fact that they possess not only the right but also the duty to revisit history in its entirety and to pose novel questions to it, in tune with the spirit of the times in which we live.